2017
DOI: 10.20960/nh.978
|View full text |Cite
|
Sign up to set email alerts
|

A new fructose-free, resistant-starch type IV-enriched enteral formula improves glycaemic control and cardiovascular risk biomarkers when administered for six weeks to elderly diabetic patients

Abstract: CM, Pérez-Rodríguez M, Pérez-de-laCruz AJ, Gil Á. A new fructose-free, resistant-starch type IV-enriched enteral formula improves glycaemic control and cardiovascular risk biomarkers when administered for 6 weeks to elderly diabetic patients. AbstractBackground: Reducing the dietary glycaemic response has been proposed as a way to reduce the risk of diabetes complications. Objective: The aim of the present study was to evaluate the glycaemic control and cardiovascular risk biomarkers in fragile, elderly type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…The mean decrease in HbA1c in our results was 0•3 %, similar to the decrease reported in other studies (32,33) . In our study, these effects were observed without any change in the anti-diabetic medication.…”
Section: Variablessupporting
confidence: 92%
See 1 more Smart Citation
“…The mean decrease in HbA1c in our results was 0•3 %, similar to the decrease reported in other studies (32,33) . In our study, these effects were observed without any change in the anti-diabetic medication.…”
Section: Variablessupporting
confidence: 92%
“…In elderly fragile patients with type 2 diabetes, who used an enteral diabetes-specific formula containing RS IV for 6 weeks, a reduction in the dietary glycaemic response has been proposed as a way to explain the response to the risk of diabetes complications (32) . HbA1c, E-selectin and monocyte chemo attractant protein-1 were significantly decreased, tending to decrease the soluble vascular cell adhesion molecule and plasminogen activator inhibitor-1.…”
Section: Variablesmentioning
confidence: 99%
“…Our results were in accordance with previous reports of Azad et al 50 who have shown an increase in myocardial malonyldialdehyde and a decrease in antioxidant enzyme activities after aluminium phosphide treatment. 58 Co-exposure to aluminum and acrylamide caused an important increase in the plasma TC and LDL-C levels and a decrease in HDL-C and TG, which indicated a change in the permeability of hepatic cells as reported in our previous study. This improvement was more pronounced in rats treated with EVOO than OOLF and OOHF used separately reflecting the synergic effect of the two fractions in order to restore the activities of anti-oxidant enzymes.…”
Section: Discussionsupporting
confidence: 82%
“…Although mean blood glucose levels were lowered with RS4 consumption, the differences did not approach statistical significance compared to the control. Mesa Garcia and her colleagues have taken a step ahead of research to study a new fructose-free DSF in fragile elderly T2DM patients for 6 wks and evaluate the influence of total enteral feeding on the glycemic control and diabetes-derived cardiovascular risk biomarkers ( 48 ). These new fructose-free DSF and RS4-enriched DSF formulations effectively controlled glycemic by decreasing blood HbA1c, and some improvements were documented in MCP-1, sE-selectin, and sVCAM-1 and PAI-1 plasma levels.…”
Section: Discussionmentioning
confidence: 99%